Form Follows Culture: Symbolic Feng Shui Logo Design in the Greater China Region - ShawHong SER (Bina Nusantara University, 2020)
The visual identity of a logo has always been one of the major means of expression of social values, and cultural preferences in a particular society. Hence, each area and region logo’s design aesthetic is a style characterized by a particular cultural influence that introduces its principles and canons. Accordingly, a logo is not just a representation of a company or business, in order to fully serve its purpose, the logo representation must illustrate what the company does as well as be able to echo with the social, cultural and geographical features of the targeted region. In this paper, to respond to the research scholarly interest in the cultural influences on design, the researcher has made an attempt to study the influence of Feng Shui on logo design in the Greater China region. Based on an in-depth visual-based survey on banks’ logo design in the Greater China region, the author identified in this paper one unique design characteristic, namely Symbolic Feng Shui logo design. The result showed that (1) there is substantial cultural values and preference for the logo with the influence and application of Feng Shui. (2) Logos based on concepts and forms (particularly ancient Chinese coins) found in Feng Shui were the most preferred visual representation used by banks in the Greater China region. (3) The Symbolic Feng Shui logo as a unique design language has developed into its distinctive style. It is hoped that this paper will provide insights into an understanding of the impact of traditional culture on modern design, particularly on Feng Shui culture-inspired logo design in the Greater China region.